Acute-Onset Chest Pain in a 17-Year-Old Female Adolescent With Systemic Lupus Erythematosus. Issue 5 (May 2017) - Mangus, Courtney W.; Fatusin, Oluwatosin; Ngo, Thuy L.
Abstract : Abstract: We report the case of a 17-year-old adolescent girl with systemic lupus erythematosus with disseminated pneumococcal infection leading to purulent pericarditis with cardiac tamponade. Although pericarditis is not an uncommon entity in autoimmune diseases such as systemic lupus erythematosus, purulent pericarditis is a rare cause (<1%) of this presentation.